Common Responses of Tumors and Wounds to Hypoxia. Issue 2 (March 2015) - Payen, Valéry L.; Brisson, Lucie; Dewhirst, Mark W.; Sonveaux, Pierre
<x xml:space="preserve">Abstract</x> Abstract Hypoxia is a characteristic of tumors and wounds. Hypoxic cells develop 2 common strategies to face hypoxia: the glycolytic switch and the angiogenic switch. At the onset of hypoxia, alleviation of the Pasteur effect ensures short-term cell survival. Long-term hypoxic cell survival requires a further acceleration of the glycolytic flux under the control of hypoxia-inducible factor 1 that stimulates the expression of most glycolytic transporters and enzymes, uncouples glycolysis from the TCA cycle, and rewires glycolysis to lactic fermentation. Hypoxic cells also trigger angiogenesis, a process that aims to restore normal microenvironmental conditions. Transcription factors (hypoxia-inducible factor 1, nuclear factor κB, activator protein 1) and lactate cooperate to stimulate the expression of proangiogenic agents. Cancer cells differ from normal hypoxic cells by their proliferative agenda and by a high metabolic heterogeneity. These effects in tumor account for further molecular and metabolic changes and for a persistent stimulation of angiogenesis.